Right to Read Implies Opportunity to Read: A Contribution to the Ongoing Dialogue Concerning the Ontario Human Rights Commission Right to Read Report - Cummins, Jim (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2023)
This paper extends discussion of the Ontario Human Rights Commission (OHRC) (2022a, 2022b) report entitled Right to Read, which recommended significant changes to both reading instruction and special education programs aimed at providing equitable opportunities for all children to develop strong reading skills. In a critique of the OHRC report (Cummins, 2022), I endorsed the report’s call for the establishment of an identification and intervention infrastructure to support students who are struggling to develop reading skills. However, I also critiqued the report’s misrepresentation of the strong reading achievements of Ontario students and the scapegoating of “balanced literacy.” Klein (2022) disputed this characterization of the OHRC report, highlighting the important contributions of the report to special education policies. In continuing this dialogue, I argue that the OHRC report has omitted consideration of significant dimensions of literacy acquisition and development that are directly relevant to preventing reading difficulties among Ontario children. Specifically, I argue that beyond the systematic teaching of phonics and other foundational literacy skills, which the OHRC report emphasizes almost exclusively, literacy policies should ensure that all children experience extensive opportunities for literacy socialization, which must involve active engagement with print, in both the preschool and early elementary years.